Dental and Oral Pathology - Slootweg, Pieter (Encyclopedia of Pathology, 2016)
This book covers the complete field of oral and maxillofacial pathology - from Addisons disease to Zimmerman-Laband syndrome. The alphabetically arranged entries, each of which provides a detailed description of a specific pathological disease pattern, allow readers to quickly and easily find the information they need.